Different association between intentionality competence and prefrontal volume in left- and right-handers - Powell, J; Kemp, G; Dunbar, R; Roberts, N; Sluming, V; García-Fiñana, M (Elsevier, 2014)
Intentionality is the ability to explain and predict the behaviour of others by attributing to them mental states, and is thus important for social cognition. Prefrontal cortex (PFC) including orbital and dorsal regions is implicated in a range of social and metacognitive executive functions (EFs). We investigate, for the first time, in 39 left-handers and 43 right-handers the effect of handedness on the relationship between intentionality and (i) PFC volume using stereology and (ii) grey matter (GM) volume within six a priori regions of interest using voxel-based morphometry (VBM). Although no association was found between degree of handedness and intentionality competence (p = .17), handedness groups differ significantly in the relationship between intentionality and PFC volume. Right-handers with handedness score =+75 (based on a range from −100 to +100) show a significant positive correlation between intentionality and orbital PFC volume (p = .01), while no significant correlation is observed for dorsal PFC volume (p = .82); and left-handers with handedness score =−75 show a significant positive correlation between intentionality and dorsal PFC volume (p = .02) while no significant correlation is observed for orbital PFC volume (p = .44). VBM results showed significantly greater GM volume correlated with intentionality in right-handers compared to left-handers (family-wise error – FWE, p < .05) in right temporo-parietal junction and superior temporal sulcus. Correlations between GM volume and intentionality were found across all subjects (FWE, p < .05) in bilateral middle frontal gyrus, superior temporal sulcus and right inferior frontal gyrus, superior frontal gyrus and precuneus. Overall, the findings suggest that the neuroanatomy underlying intentionality competence is influenced by handedness and that different methodological approaches can and should be considered in conjunction when investigating neuroanatomical correlates of psychological functioning.